THE SIMULATED MODEL AND PREDICTED TENDENCIES OF ACCRETION- EROSION, CHANGES OF BOTTOM TOPOGRAPHY IN THE COASTAL ZONE FROM HOA DUAN TO HAI DUONG, THUA THIEN HUE PROVINCE - Thanh, Le Van (Vietnam Journal of Marine Science and Technology, 2006)
THE SIMULATED MODEL AND PREDICTED TENDENCIES OF ACCRETION- EROSION, CHANGES OF BOTTOM TOPOGRAPHY IN THE COASTAL ZONE FROM HOA DUAN TO HAI DUONG, THUA THIEN HUE PROVINCE